2015
DOI: 10.5935/medicalexpress.2015.05.04
|View full text |Cite
|
Sign up to set email alerts
|

Globally chaotic analysis of Heart Rate Variability during acute auditory stimulus by heavy metal music

Abstract: OBJECTIVE:Auditory stimulation with relaxing style music can improve cardiac autonomic regulation in subjects treated with a cardio-toxic medication. We assess the acute effect of heavy metal music on cardiac autonomic regulation, through novel high spectral chaotic global analysis techniques: (a) high spectral detrended fluctuation, (b) high spectral entropy (c) spectral multi-taper method. METHOD: We investigated young adult women between 18 and 30 years old exposed to heavy metal (75-84 dB) music for 20 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
3
0
3
Order By: Relevance
“…A previous study reported that chaotic global analysis was unable to identify HRV changes during mental task [59]. Another research study investigated chaotic global analysis in RR intervals during exposure to heavy metal music [60]. The authors failed to reveal influences of this music style on the complexity of HRV.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study reported that chaotic global analysis was unable to identify HRV changes during mental task [59]. Another research study investigated chaotic global analysis in RR intervals during exposure to heavy metal music [60]. The authors failed to reveal influences of this music style on the complexity of HRV.…”
Section: Discussionmentioning
confidence: 98%
“…Outro estudo avaliou o efeito de uma intervenção musical sobre a ansiedade e parâmetros vitais em 60 pacientes com idade igual ou superior a 18 anos com doença renal crônica em comparação ao cuidado de clínicas de hemodiálise, concluiu que o estímulo musical infere ter potencial de intervenção para a redução do estado de ansiedade durante sessões de hemodiálise (Melo et al, 2018). Já em outro estudo que avaliou o efeito agudo da música heavy metal na regulação autonômica cardíaca em mulheres adultas jovens entre 18 e 30 anos expostas a músicas "pesadas" (75-84 dB) por 20 min, sugeriu que a estimulação musical aguda com música "pesada" influencia a regulação autonômica cardíaca em um nível mais complexo sendo benéfico para a função cardíaca (Nogueira et al, 2015).…”
Section: Discussionunclassified
“…A partir de métodos lineales, la teoría del caos y el análisis fractal se han desarrollado nuevas metodologías para el estudio de las dinámicas fisiológicas [32][33][34][35][36][37][38] , con esto se han logrado contribuciones importantes, entre ellas, una nueva concepción de normalidad enfermedad 15 , así como mejores predictores de mortalidad, y nuevos índices para cuantificar la complejidad de las dinámicas estudiadas, sin embargo es necesario realizar más estudios para establecer su aplicabilidad clínica 39,40 .…”
Section: Discussionunclassified